A Herbal Formula HT051, a Combination of Pueraria lobata and Rehmannia glutinosa, Prevents Postmenopausal Obesity in Ovariectomized Rats. (26th December 2017) - Lee, Yoon Hee; Jin, Bora; Lee, Sunghyun; Oh, Jin-Young; Song, Jungbin; Lee, Donghun; Kim, Young-Sik; Kim, Hocheol
Abstract : Menopause is strongly associated with an increased risk of metabolic dysfunctions due to the decline in estrogen. Here, we hypothesized that dietary HT051, containing the roots of Pueraria lobata and Rehmannia glutinosa, has beneficial effects on ovariectomized (OVX) rats by regulating lipid metabolism. Forty-eight female Sprague-Dawley rats were randomly divided into 4 groups: sham-operated (Sham), OVX, OVX with low-dose HT051 supplementation, and OVX with high-dose HT051 supplementation. The rats were fed with a modified AIN-93G diet or an HT051-containing modified AIN-93G diet for 8 weeks. Body weight, fat mass, and serum levels of total cholesterol, triglyceride, glucose, alanine transaminase, and aspartate transaminase decreased in HT051-fed OVX rats. Dietary HT051 supplementation significantly decreased the mRNA expression of lipogenesis-related genes, including sterol regulatory element-binding protein 1c and fatty acid synthase, and increased the mRNA expression of β -oxidation-related genes, including peroxisome proliferator-activated receptor and carnitine palmitoyl transferase 1 in the liver of OVX rats. Moreover, the expression of genes involved in adipogenesis and inflammation was significantly lower in the adipose tissue of OVX rats fed with HT051 than in the OVX group. These findings suggest that HT051 may be a potential natural alternative for the management of postmenopausal metabolic dysfunctions.